2010
DOI: 10.1021/mp100068s
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Microemulsion Components into the Stratum Corneum and Their Molecular Effects on Skin Barrier Function

Abstract: This research determined the uptake of individual components of topically applied microemulsions into the stratum corneum (SC) and assessed their molecular effects on skin barrier function. The microemulsions comprised oleic acid, Tween20, Transcutol and water. The effects of selected formulations, and of the individual components, on the conformational order of the SC intercellular lipids, and on SC hydration, were assessed by infrared spectroscopy. Measurements were made as a function of SC depth by progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 28 publications
4
55
0
Order By: Relevance
“…The use of Transcutol ® in topical and transdermal drug delivery has been examined widely due to its nontoxicity and optimal solubilizing parameters for a number of drugs. [29][30][31][32] It is well known that microemulsion structures are strongly dependent on the ratio of the constituents. Pseudoternary phase diagrams can be used to note the physical boundary conditions (microemulsion, liquid crystalline, micelles) of oil, surfactants, and water necessary to formulate stable formulations.…”
Section: Results and Discussion Preparation And Characterization Of Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of Transcutol ® in topical and transdermal drug delivery has been examined widely due to its nontoxicity and optimal solubilizing parameters for a number of drugs. [29][30][31][32] It is well known that microemulsion structures are strongly dependent on the ratio of the constituents. Pseudoternary phase diagrams can be used to note the physical boundary conditions (microemulsion, liquid crystalline, micelles) of oil, surfactants, and water necessary to formulate stable formulations.…”
Section: Results and Discussion Preparation And Characterization Of Fmentioning
confidence: 99%
“…It has been reported that oleic acid fluidizes the stratum corneum intercellular lipids and induces phase separation, and thereby exerts a penetration enhancing effect. 31,37,40,41 Together with the oleic acid reported effects, the partitioning of the surfactant (Kolliphor ® EL or Kolliphor ® RH40) and the cosurfactant (Transcutol ® ) may have also contributed to the C-H symmetric and asymmetric blue shifts. The C-H symmetric stretching frequencies are known to be more susceptible to changes in lipid matrix organization.…”
mentioning
confidence: 99%
“…Interestingly, two contradicting observations were found to be prevalent in this composition. Firstly, it contained the maximum amount of Tween 80 (46.67%), out of all the studied compositions, which is reported to emulsify sebum and extract skin lipids that enhance the thermodynamic coefficient of the drug, allowing it to penetrate into the cells more effectively (45,46). On the other hand, the amount of phospholipid was observed to be least in G15 (7.78%).…”
Section: Ex Vivo Skin Permeation Studiesmentioning
confidence: 97%
“…Moreover, the enhancing activities of these l-carvyl esters were evaluated using the model drug 5-fluorouracil (FU) in the in vitro skin permeation experiment. Several researchers agree that the enhancing activity of an enhancer may be determined by the amount of its uptake into the SC (11)(12)(13). However, the amount of an enhancer retained in the skin is rarely measured.…”
Section: Introductionmentioning
confidence: 99%